2008
DOI: 10.1111/j.1439-0388.2007.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Bovine Growth Hormone Gene to Carcass Traits in Japanese Black Cattle

Abstract: The bovine growth hormone gene (bGH) possesses three haplotypes, A, B and C, that differ by amino acid mutations at positions 127 and 172 in the fifth exon: (leucine 127, threonine 172), (valine 127, threonine 172) and (valine 127, methionine 172) respectively. The correlation between meat quality or carcass weight and these haplotypes was investigated in Japanese black cattle. Altogether, 940 bGH haplotypes were compared with respect to six carcass traits: carcass weight, longissimus muscle area, rib thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 13 publications
2
27
0
2
Order By: Relevance
“…Therefore, the substitution of leucine (L allele) by valine (V allele) leads to the appearance of 3 genotypes of the GH gene and produces different physiological processes (19). Consequently, it has been reported that the GH gene may be an indicator for meat production traits, denoting that it could be used for the genetic improvement of beef cattle (12). Nevertheless, it has also been reported that the polymorphisms at GH are not a sufficient tool for the selection of beef cattle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the substitution of leucine (L allele) by valine (V allele) leads to the appearance of 3 genotypes of the GH gene and produces different physiological processes (19). Consequently, it has been reported that the GH gene may be an indicator for meat production traits, denoting that it could be used for the genetic improvement of beef cattle (12). Nevertheless, it has also been reported that the polymorphisms at GH are not a sufficient tool for the selection of beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it plays an indirect role in cell growth (5). Therefore, GH polymorphism has been considered by researchers to affect weight gain, carcass weight, birth weight, and carcass quality such as marbling (12,18). Due to the crucial role of GH in lactation and animal growth, the GH gene is thought to be a candidate marker for performance traits in livestock animals such as cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growth hormone (GH) gene is one of those genes: It encodes growth hormone, which has important roles in control of the body metabolism (Moravčiková et al, 2012). Growth Hormone directly or indirectly plays a role in tissue growth and fat metabolism, so that it has an important role in growth traits, reproduction and lactation in cattle (Tatsuda et al, 2008). The growth hormone is a single-chain polypeptide consisting of 191 amino acids that is synthesized and secreted by the anterior pituitary gland (Nicoll et al, 1986;Moravčiková et al, 2012).…”
Section: Introductionmentioning
confidence: 99%